2020
DOI: 10.1108/lodj-07-2019-0287
|View full text |Cite
|
Sign up to set email alerts
|

Leader humility and employee organizational deviance: the role of sense of power and organizational identification

Abstract: PurposeThe authors examined the relationship between leader humility and employee organizational deviance. They also tested the mediating effects of personal sense of power and the moderating effects of organizational identification on this relationship.Design/methodology/approachThe authors tested their hypotheses using a sample of 186 employees from an information technology (IT) enterprise in China. They used hierarchical regression and bootstrapping analyses to test for direct and indirect relationships.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 60 publications
(89 reference statements)
2
49
0
2
Order By: Relevance
“…For example, Abbasi et al (2020) used SIT to explain the moderating role of organizational identification in the relationship between high-performance work systems and psychological empowerment. Other studies have suggested that organizational identification moderates the relationship between high-performance human resource practices and volunteer engagement (Traeger and Alfes, 2019), compulsory citizenship behaviors (CCB) and their impact on employee silence (He et al, 2018), reducing the effect of the sense of empowerment on deviant behaviors (Qiuyun et al, 2020). Thus, in this study, organizational identification was used as the moderating variable to examine the influence of IWEs on knowledge-sharing behaviors and the following hypotheses were proposed: JIABR 12,8…”
Section: Moderating Effect Of Organizational Identificationmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Abbasi et al (2020) used SIT to explain the moderating role of organizational identification in the relationship between high-performance work systems and psychological empowerment. Other studies have suggested that organizational identification moderates the relationship between high-performance human resource practices and volunteer engagement (Traeger and Alfes, 2019), compulsory citizenship behaviors (CCB) and their impact on employee silence (He et al, 2018), reducing the effect of the sense of empowerment on deviant behaviors (Qiuyun et al, 2020). Thus, in this study, organizational identification was used as the moderating variable to examine the influence of IWEs on knowledge-sharing behaviors and the following hypotheses were proposed: JIABR 12,8…”
Section: Moderating Effect Of Organizational Identificationmentioning
confidence: 95%
“…A large body of empirical evidence suggests that the relationship between the work environment, organizational factors and workplace behaviors is moderated by organizational identification (Abbasi et al, 2020;Agarwal and Farndale, 2017;He et al, 2018;Qiuyun et al, 2020;Traeger and Alfes, 2019). For example, Abbasi et al (2020) used SIT to explain the moderating role of organizational identification in the relationship between high-performance work systems and psychological empowerment.…”
Section: Moderating Effect Of Organizational Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such diminished organizational identification in turn may steer employees towards counterproductive work behaviours [1]. Deviant work activities represent pertinent behavioural responses, through which employees with negative feelings about their organization can unleash these feelings (Al-Atwi and Bakir, 2014;Qiuyun et al, 2020). In particular, limited identification with their organization may spur deviant work activities as a means to express disappointment about this missing psychological connection (Ciampa et al, 2019;Erkutlu and Chafra, 2018;Penney and Spector, 2005).…”
Section: Mediating Role Of Organizational Identificationmentioning
confidence: 99%
“…Second, prior research argues that organizational deviance is more harmful for organizational health, progress and prosperity (e.g. Javed et al , 2019; Qiuyun et al , 2020).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%